2020
DOI: 10.3390/foods9030255
|View full text |Cite
|
Sign up to set email alerts
|

Development of Head Space Sorptive Extraction Method for the Determination of Volatile Compounds in Beer and Comparison with Stir Bar Sorptive Extraction

Abstract: A headspace sorptive extraction method coupled with gas chromatography–mass spectrometry (HSSE–GC–MS) was developed for the determination of 37 volatile compounds in beer. After optimization of the extraction conditions, the best conditions for the analysis were stirring at 1000 rpm for 180 min, using an 8-mL sample with 25% NaCl. The analytical method provided excellent linearity values (R2 > 0.99) for the calibration of all the compounds studied, with the detection and quantification limits obtained being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Indeed, all of these previously mentioned metabolites are frequently detected in beer volatile composition [46,50], being their main source related with yeast metabolism [55,56]. Moreover, these results are in agreement with those reported by Ruvalcaba et al [49], which showed a similar set of metabolites that had the highest concentration in beers, namely, 3-methyl-1-butanol, ethyl octanoate, ethyl hexanoate, 3-methylbutyl acetate, 2-phenylethyl acetate, and octanoic acid.…”
Section: Profiling the Lager Beer Volatile Metabolitessupporting
confidence: 91%
“…Indeed, all of these previously mentioned metabolites are frequently detected in beer volatile composition [46,50], being their main source related with yeast metabolism [55,56]. Moreover, these results are in agreement with those reported by Ruvalcaba et al [49], which showed a similar set of metabolites that had the highest concentration in beers, namely, 3-methyl-1-butanol, ethyl octanoate, ethyl hexanoate, 3-methylbutyl acetate, 2-phenylethyl acetate, and octanoic acid.…”
Section: Profiling the Lager Beer Volatile Metabolitessupporting
confidence: 91%
“…In the present study a total of 40 volatile compounds have been quantified in the various samples analysed, which mainly belong to the family of esters, alcohols, aldehydes and acids (supporting information, Table S2). All the volatile compounds determined had previously been found in both high and low fermentation beer samples 12,25–28 …”
Section: Resultsmentioning
confidence: 89%
“…The optimization of the extraction parameters was performed using aldehydes standards (1.0 mg/L) prepared in model solutions (5% ethanol). The experiments started with the study of the impact of time (5,10,20, and 30 min) and temperature (40, 50, and 60 • C) on extraction for both DNPH and HBA.…”
Section: Extraction Conditions Studymentioning
confidence: 99%
“…The analysis of flavor compounds in beer has been continuously optimized to achieve better sensitivity and specificity. In the last 10 years, different extraction techniques have been applied for the analysis of carbonyl compounds in alcoholic beverages, such as headspace solid-phase microextraction (HS-SPME) [17,18] and stir bar sorptive extraction (SBSE) [19,20]. Derivatization techniques are also a good strategy to improve the volatility and extraction of semi-volatile compounds, as well as to improve its stability [21] and detectability during LC-UV analysis [22].…”
Section: Introductionmentioning
confidence: 99%